The effects of ASEAN Free Trade Agreement (AFTA) on intra ASEAN trade: 1986-2010 - Ismail, Normaz Wana; Wong, Collin Koh King (Universiti Putra Malaysia Press, 2013)
The ASEAN Free Trade Agreement (AFTA) was set up in 1993 and has already shown significant effects by 2010. This study empirically investigates the effect of trade creation on intra-ASEAN trade for the period of 1986 to 2010. Using the gravity model, we find that major determinants of bilateral trade in ASEAN are GDP, population, relative endowment, distance and common border. A dummy variable is introduced to measure the intra-ASEAN trade and trade creation among five ASEAN member countries. Our finding suggests that trade between the selected member countries remains strong even during the 1997 Asian Financial Crisis and the 2008 Global Financial Crisis.